Language representation of emotions as a means of personalizing in the poetic speech of Arcadiy Kazka - Янченко, Юлія Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The study contains a structural analysis of emotive language means acting as representantatives of personalizing a poetic speech of Arcadiy Kazka. The semantic groups of tokens are higheighted which transmit and show the speaker’s emotions. It was found that personalization tool is dominant in the poetic texts of the representatives of «Executed renaissance».